2009
DOI: 10.1111/j.1468-1293.2009.00744.x
|View full text |Cite
|
Sign up to set email alerts
|

A 5‐year longitudinal follow‐up study of serological responses to 23‐valent pneumococcal polysaccharide vaccination among patients with HIV infection who received highly active antiretroviral therapy*

Abstract: BackgroundLong-term antibody responses to 23-valent pneumococcal polysaccharide vaccine (PPV) among HIV-infected patients receiving highly active antiretroviral therapy (HAART) are rarely investigated. MethodsAntibody responses to three pneumococcal capsular polysaccharides [Pneumococcal polysaccharide (PPS) 14, 19F and 23F] were assessed among 169 HIV-infected patients who received HAART and 23-valent PPV. Patients were stratified into four groups according to CD4 count at vaccination: group 1, CD4o100 ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
1
9

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(39 citation statements)
references
References 40 publications
(137 reference statements)
2
26
1
9
Order By: Relevance
“…[5][6][7] Moreover, the only randomized clinical trial of vaccination with 23-valent PPV among HIV-infected Ugandan adults without receiving cART did not demonstrate clinical benefits in subjects who received 23-valent PPV compared with those who received placebo. 8 The widespread use of pneumococcal conjugate vaccine (PCV) since its licensure has significantly reduced the incidence of invasive pneumococcal disease both in HIV-uninfected and HIV-infected children.…”
Section: Serologic Response To Primary Vaccination With 7-valent Pneumentioning
confidence: 93%
“…[5][6][7] Moreover, the only randomized clinical trial of vaccination with 23-valent PPV among HIV-infected Ugandan adults without receiving cART did not demonstrate clinical benefits in subjects who received 23-valent PPV compared with those who received placebo. 8 The widespread use of pneumococcal conjugate vaccine (PCV) since its licensure has significantly reduced the incidence of invasive pneumococcal disease both in HIV-uninfected and HIV-infected children.…”
Section: Serologic Response To Primary Vaccination With 7-valent Pneumentioning
confidence: 93%
“…32 The loss of the antibodies induced by the nonconjugated polysaccharide vaccine occurs particularly rapidly in the most severely immunocompromised patients or in patients not (Continued on next page) virologically controlled by cART. 33 Conjugated vaccines induce higher immunogenicity and have been tested in HIV-infected patients. A randomized double-blind placebo-controlled clinical trial in HIV-infected adults conducted in Malawi demonstrated the efficacy of 2 doses of the 7-valent conjugate vaccine, which reduced invasive pneumococcal infections by 74% in secondary prophylaxis.…”
Section: Pneumococcal Vaccinationmentioning
confidence: 99%
“…62 Significant decline in immune responses was observed in HIV-infected patients receiving cART 5 y after primary vaccination with PPV23, especially in patients with CD4 <100 cells/ml and uncontrolled HIV replication. 38 Therefore, several studies have examined the immunogenicity of revaccination with PCV in HIV-infected patients who have received PPV before. 41,54,56 The first study in Uganda by Miiro et al compared the immunogenicity of 2 doses of PCV7 (4 weeks apart) versus placebo in HIV-infected adults who have received PPV23 3.5 to 6.6 y (median 5.2 years) earlier.…”
Section: Pcv Revaccination In Hiv-infected Adults Who Have Received Pmentioning
confidence: 99%
“…Despite the limitations by the heterogeneity of study design and execution of these observational studies, the authors concluded that currently available evidence is only moderate to support the routine use of PPV23 in HIV-infected patients and newer or more immunogenic vaccines are needed. 8 With respect to immunogenicity of PPV23, the results of published studies are summarized in Table 1, [31][32][33][34][35][36][37][38][39][40][41] which are much more difficult to interpret than the clinical effectiveness studies because of differences in study design, comparators enrolled, CD4 counts and receipt of antiretroviral therapy, especially cART, of the subjects, pneumococcal serotypes assessed, timing of blood sampling, follow-up duration, methods to assess the response (enzyme-linked immunosorbent assay [ELISA] or opsonophagocytic activity [OPA] assay), definitions used for immune response (fold rise of antibody, antibody concentration, or geometric mean concentration or titer). Despite the renumeration of CD4 counts with cART, several studies have shown that most patients failed to maintain durable antibody response for most serotypes following vaccination with PPV23 over the 5-year follow-up period, especially those who had low CD4 counts at vaccination and uncontrolled HIV replication.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation